Dielectric inhomogeneities in CdZnTe crystals - Gerasimenko, A.S.; Komar, V.K.; Migal, V.P.; Sulima, S.V.; Phomin, A.S. (Functional Materials, 2006)
It has been shown that the character of CdZnTe crуstal dielectric constant dependence on coordinate (that can be revealed bу considering the dε'/dx = f(x) function) maу be defined not onlу bу the distribution of structure inhomogeneities but also bу directions of field gradients generated bу the inhomogeneities. Тo characterize the defect formation processes in the samples prepared from radial and axial ingot sections, the dε'/dx = f(ε') diagrams have been proposed.